Being human: responding to changes - Sedu, Nerawi (Partridge, 2019)
Changes, whether technological or social or cultural, happen continuously in every society, and they change how members of the society live their lives. This book, which is research based, discusses how changes affect societies and individuals in terms of their practices and rituals as well as the way they view the world. It consists of seven chapters written by eleven authors with different educational background and academic disciplines. The writings in this book highlight how different communities in different countries (i.e., Malaysia, Pakistan, and Philippines) change and modify their traditional practices and worldviews in order to meet the technological and societal demands. This book is a good reading to those who are interested to understand humans’ capability for change in preserving and sustaining their lifestyles and Weltanschauung in the ever changing and challenging world.